Thermohaline instability and the formation of glacial North Atlantic super polynyas at the onset of Dansgaard‐Oeschger warming events - Guido Vettoretti; W. Richard Peltier (Geophysical Research Letters)
Abstract Late Quaternary rapid warming events inferred on the basis of oxygen isotopic data from Greenland ice cores are the most prominent characteristic of millennial‐scale Dansgaard‐Oeschger oscillations. In a coupled climate model simulation which has accurately reproduced this oscillatory behavior for the first time, we show that formation of a glacial North Atlantic super polynya characterizes the initial stage of transition from cold stadial to warm interstadial conditions. The winter polynya forms within the otherwise sea ice‐covered North Atlantic as a consequence of the onset of a thermohaline convective instability beneath an extensive stadial sea ice lid. Early in the stadial period, the tendency for thermal convective instability of an extensive warm pool beneath the sea ice lid is strongly inhibited by a stabilizing vertical salinity gradient, which gradually diminishes until a thermohaline convective instability occurs that leads to polynya formation and the rapid retreat of North Atlantic sea ice cover.